2011
DOI: 10.1007/s10067-011-1795-1
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of biocorrelates for brain involvement in female patients with rheumatoid arthritis

Abstract: Central nervous system (CNS) abnormalities are rare in patients with rheumatoid arthritis (RA). Direct studies done to investigate brain involvement in RA are few or even absent. We hypothesized that CNS is not excluded from the inflammatory disease process in RA. Thus we systematically investigated markers of brain involvement in 55 females with RA. We examined patients' cognition using battery of sensitive psychometric testing [Mini-Mental State Examination, Stanford-Binet test (fourth edition) and Wechsler … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
29
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(35 citation statements)
references
References 43 publications
5
29
0
Order By: Relevance
“…The mean education level ranged from 1.8 to 15.1 years across 10 studies, with 2 not having provided details on education (34,36) and 3 having provided only prevalence rates (more than 8 years [23] and fewer than 12 years [30,31]). Of the 15 studies, 3 (30,31,33) stated the prevalence of cognitive impairment (30%, 0%, and 31%, respectively), while some of the other studies only reported reduced test scores (34,40) or impairment rates across individual tests (32) or combined groups' rates (42) ( Table 4 (Table 5). Effect sizes are broadly classified into small, medium, and large indicators of standardized differences (44).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The mean education level ranged from 1.8 to 15.1 years across 10 studies, with 2 not having provided details on education (34,36) and 3 having provided only prevalence rates (more than 8 years [23] and fewer than 12 years [30,31]). Of the 15 studies, 3 (30,31,33) stated the prevalence of cognitive impairment (30%, 0%, and 31%, respectively), while some of the other studies only reported reduced test scores (34,40) or impairment rates across individual tests (32) or combined groups' rates (42) ( Table 4 (Table 5). Effect sizes are broadly classified into small, medium, and large indicators of standardized differences (44).…”
Section: Resultsmentioning
confidence: 99%
“…The inclusion, measurement, and severity of clinical variables varied considerably across studies. The following variables were found to be associated with cognitive function: pain (23,29,31,36,38), disease activity (32,33), fatigue (37), medication (prednisone/steroids [31,40] and MTX [30]), biomarkers (interleukin-6, B cells, and T cells) (34,35,40), and cardiovascular disease risk factors (30). A range of assessment tools was used across studies, prohibiting systematic comparison of clinical profile across samples.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In inflammatory diseases of the gut, S100B expression is strongly increased (41) and dose-dependently induces the expression of iNOS, with optimal NO production at 500-5000 nM S100B (44). In vivo, patients with rheumatoid arthritis patients show micromolar S100B serum concentrations (48), and patients with Alzheimer disease or HIV infection show micromolar concentrations of S100B in the cerebrospinal fluid (49). Lymphocytes as well as glioma cells and hippocampal tissue can produce and secrete S100B upon stimulation (50-53) with IL-1b and other proinflammatory cytokines.…”
Section: Discussionmentioning
confidence: 99%
“…These include obesity (Miller and Spencer, 2014), HIV infections (Correia et al, 2013;Hilsabeck et al, 2010), healthy older adults (Elderkin-Thompson et al, 2012;Noble et al, 2010;Simpson et al, 2013), chemotherapy (Cheung et al, 2013;Ganz et al, 2013;Kesler et al, 2013), heart failure (Athilingam et al, 2013), RA (Hamed et al, 2012), hepatitis C virus infection (Farag et al, 2011) and bipolar disorder (Bauer et al, 2014;Lotrich et al, 2014).…”
Section: Cognitive and Memory Difficulties And Inflammationmentioning
confidence: 99%